AHP 기법을 이용한 해상교통관제 업무의 상대적 중요도 및 작업부하 평가 - 김광일; 김주성 (한국해양경찰학회보, 9(2), 2019)
해상교통관제업무는 정보의 수집과 수집한 정보의 가공, 그리고 가공한 정보의 제공 과정에서 이루어진다. 우리나라는 1993년 포항항에 최초의 해상교통관제센터를 설립한 이후 2018년 현재 전국에 20개 센터를 운영 중이다. 해상교통관제업무는 선박의교통 집중과 더불어 점차 그 업무의 기능적 영역이 확대되고 있다. 그러나 관제 섹터의 분류, 인력의 운용 등에 대한 명확한 근거가 부족한 실정이고, 각 센터의 관제 운영 관행이나 내부 지침에 따라 운영되고 있다. 본 논문에서는 관제 영역의 설정과 인력 운용에 대한 근거 확보를 위하여 해상교통관제 업무를 분류하고, 각 업무에 대한해상교통관제사의 상대적 업무 중요도 및 작업 부하에 대하여 분석하였다. 상대적 중요도 및 작업 부하를 측정하기 위하여 다기준의사결정 기법인 계층화분석기법을 사용하였으며, 데이터 수집 방법은 전국 해상교통관제센터에서 근무하는 해상교통관제사373명을 대상으로 설문과 심층 인터뷰를 수행하였다. 분석 결과 해상교통관제 업무의평가 기준과 하위 평가 기준에 따라 상대적 중요도와 작업 부하의 가중치를 도출하였다. 본 연구 결과를 통하여 업무의 중요도에 따른 발생 빈도와 그에 따른 작업자의작업 부하에 따라 인력을 배치하고 근무방식을 결정하는 등 향후 관제 영역 설정의가중치 또는 중요도와 작업부하의 관계를 바탕으로 섹터 운영의 기초 자료로 활용할수 있을 것으로 기대한다. The tasks of Vessel Traffic Services consists the collection of information, the processing of collected information, and the provision of processed information. Since the establishment of the first Vessel Traffic Service center in the port of Po-hang in 1993, Korea has been operating 20 centers nationwide in 2018, and its functional work domain is gradually expanding. However, there is a lack of clear grounds for the classification of operating sectors and human resource management, and it has operated according to the practices and internal guidelines of each center. In this paper, it was aimed to classify the tasks of Vessel Traffic Services and analyze the relative importance and workload of Vessel Traffic Service operators to establish the operating area and to secure the basis of personnel management. In order to measure the relative importance and workload, it was conducted a questionnaire survey using the multi criteria decision making process that is named Analytic Hierarchy Process. As a result of analysis, weight values of relative importance and workload were derived according to the criteria and sub-criteria. It is expected that the relative importance and workload of the tasks can be utilized as the data of variable sector operation or selection of Vessel Traffic Service area based on the relationship between the importance and workload. KCI Citation Count: 1